Immobilization of Aspergillus Oryzae β-galactosidase in Cation Functionalized Agarose Matrix and Its Application in the Synthesis of Lactulose - Vera-Vera, C (Elsevier B.V., 2021)
Aspergillus oryzae β-galactosidase was immobilized in in-house quaternary ammonium agarose (QAA) and used for the first time in the synthesis of lactulose. A biocatalyst was obtained with a specific activity of 24,690 IUH∙g−1; protein immobilization yield of 97% and enzyme immobilization yield of 76% were obtained at 30 °C in 10 mM phosphate buffer pH 7 for standard size agarose at 100 mgprotein∙gsupport−1 which the maximum protein load of QAA. Highest yield and specific productivity of lactulose were 0.24 g∙g−1 and 9.78 g∙g−1 h−1 respectively, obtained at pH 6, 100 IUH∙g lactose−1 enzyme/lactose ratio and 12 lactose/fructose molar ratio. In repeated-batch operation with the immobilized enzyme, the cumulative mass of lactulose per unit mass of contacted protein and cumulative specific productivity were higher than obtained with the soluble enzyme since the first batch. After enzyme activity exhaustion, the enzyme was desorbed and QAA support was reused without alteration in its maximum enzyme load capacity and without detriment in yield, productivity and selectivity in the batch synthesis of lactulose with the resulting biocatalyst. This significantly decreases the economic impact of the support, presenting itself as a distinctive advantage of immobilization by ionic interaction. © 2020 Elsevier B.V.